2012
DOI: 10.3109/02652048.2012.676092
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and applications of microcapsules obtained by interfacial polycondensation

Abstract: This review highlights the materials, mechanisms and applications of microencapsulation by interfacial polycondensation in different areas. This technology entraps active ingredients inside microcapsules/microspheres, having an average diameter ranging from nanosize to several 100 µ. Polycondensation reactions take place at the boundary of two phases to form the shells of microcapsules or matrix microspheres. The emulsion can be classified into three types: water-in-oil, oil-in-water and oil-in-oil. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 114 publications
(151 reference statements)
0
40
0
Order By: Relevance
“…We would like to apply these capsules in catalytic reactions, therefore the capsules should, on one hand, be permeable, in order to enable the reactants diffusion to the core. On the other hand, the shell should prevent leaching of the core [61][62]. We believe the PAPI 27:BAPIC molar ratio, 1.0:1.4 can provide these features and therefore further optimization was conducted using this ratio.…”
Section: Preparation Of Bmim[pf 6 ] Polyurea Microcapsules Via Bmim[pmentioning
confidence: 98%
See 3 more Smart Citations
“…We would like to apply these capsules in catalytic reactions, therefore the capsules should, on one hand, be permeable, in order to enable the reactants diffusion to the core. On the other hand, the shell should prevent leaching of the core [61][62]. We believe the PAPI 27:BAPIC molar ratio, 1.0:1.4 can provide these features and therefore further optimization was conducted using this ratio.…”
Section: Preparation Of Bmim[pf 6 ] Polyurea Microcapsules Via Bmim[pmentioning
confidence: 98%
“…SEM images show the formation of capsules in all six ratios. Several studies demonstrated that the shell thickness is highly affected by the cross-linking monomers ratio [61][62]. This affects the permeability of the capsules and their applicability in different fields.…”
Section: Preparation Of Bmim[pf 6 ] Polyurea Microcapsules Via Bmim[pfmentioning
confidence: 99%
See 2 more Smart Citations
“…This property, along with the merits of versatile and stable mechanical and chemical properties of the membrane, as well as permeability, makes this approach a promising candidate for wide applications. Therefore, a multitude of publications have been focused on its utilization, such as self-healing [36,37] agriculture [38], cosmetics [39], and pharmaceutics [40]. Mcilroy and Blaiszik [41] developed a method for the preparation of microcapsules containing a reactive amine with potential applications in self-healing polymers.…”
Section: Research Advances In Microencapsulationmentioning
confidence: 99%